Immunomodulatory effects of photothermal therapy in breast cancer: advances and challenges - Chen, Lin; Zhang, Hanyu; Hou, Yi; Yunlong, Wang; Feng, Xianhu (Frontiers in Immunology, 2025)
Breast cancer (BC) is the leading cause of cancer death in women, partly because of the significant toxicity and low specificity associated with chemotherapy drugs. Photothermal therapy (PTT) provides a new paradigm for the precise treatment of BC through local thermal ablation and immune regulation. PTT utilizes the heat generated by laser irradiation to kill tumor cells. Notably, PTT can activate the innate and adaptive immune systems by releasing antigens, which are then presented by antigen-presenting cells (APCs). These antigens are primarily released through various forms of tumor cell death induced by the thermal effects of PTT. The process of PTT-activated anti-immunity involves T cells, dendritic cells (DCs), B cells, natural killer (NK) cells, and macrophages. Therefore, regulation of the immune system by PTT in BC is considered as a promising therapeutic approach. This review elucidates the mechanisms by which PTT regulates anti-tumor immune responses through processes such as antigen release, antigen presentation, and immune cell activation. We also focus on the latest advancements and challenges in nanomaterials research, preclinical studies, and translational trials for PTT in BC treatment. This review is expected to improve our understanding of the anti-tumor effects of PTT based on the immune cycle of BC. It is expected to address critical gaps in PTT-based immunotherapy for BC, such as insufficient antigen release, the immunosuppressive microenvironment, and the transformation of cold tumors.